The Offspring Absence Factor Divorce Runs in the Family (Case Study at the Religious Court Medan in 2020) - M Rizal; Fathul Djannah (RIRAI Publisher, 2021)
Divorce is the end of a marriage. Divorce is a break in the relationship between husband and wife. Every married couple must have their ways to prevent a divorce from happening. Divorce is always based on quarrels between husband and wife. This is the reason that a dispute between husband and wife occurs because one of the parties wants a divorce, therefore the family relationship is not harmonious. Offspring who are not present in the household is very important, apart from being the successor of the heir, children are also the goal of a harmonious household, especially if certain tribes or customs require an offspring to be the successor of the family name. In this case, the applicant and the defendant both did not want to adopt a child, so they decided to divorce at Religious Court Medan